Estudo experimental sobre o uso de estribos de plástico como armadura transversal em vigas de concreto armado - Perin, Lucas Henrique (2018)
In a competitive market, the search for new materials aiming at a greater productivity with reduction of costs entails the creation of new products with unknown properties or without technical specifications. As for the example of the plastic stirrups, under study in this paper, these products appear as an alternative to the use of existing materials. Therefore, this paper compares the shear strength of concrete reinforced beams with plastic stirrups and steel stirrups as shear reinforcement, as for their theoretical and experimental resistant capacity. For this, nine beams were submitted to the Stuttgart test, being collected their failure load as well as their failure mode. The results show that plastic stirrups do not replace steel stirrups with the same efficiency. Beams reinforced with plastic stirrups had resistant capacity significantly lower than those reinforced with steel stirrups, behaving like beams without shear reinforcement. However, its use may be appropriate in structural elements with shear stress compatible with the plastic resistance, or in structural elements that refer to a minimum shear reinforcement rate.